Criminalization in Islamic Penal Code: A Study of Principles, Criminalization Methods, and Declining Variations - Danial, Danial (SCAD Independent, 2023)
This study explores the principles and methods used by the al-Qur'an in criminalizing. The method used in this research is a library method with primary data obtained from the al-Qur'an and secondary data obtained from the tafsīr books, hadith ahkām, jinayāt books, and literature on criminal law, criminology, victimology, and relevant previous research findings. The result found that the principles used by the al-Qur'an in criminalizing an act are the principles of benefit, prevention, material legality, and transcendental principles. Two methods of criminalization are used: (1) the texts of the al-Qur'an and the Hadith itself, which state that this action must be punished; (2) determined in one of three ways. (a) al-Qur'an and Hadith stipulate that this act is hazardous for society; (b) based on common sense considerations that the act could disturb public order; and (c) the act constitutes a preliminary offense for a more significant and more dangerous offense. Furthermore, it is found that the variant of the ta'zīr offense includes offenses that are related to morality, sexual crimes, crimes against religion, crimes against the body, crimes against property, crimes related to family/descent, disturbing public order, environmental crime, fraud and forgery, and traffic offense.